Evaluasi Peraturan Walikota Pekanbaru Nomor 33 Tahun 2016 Tentang Kebijakan Kota Layak Anak - Syaprianto, Syaprianto; Setiawan, Risky; Afrizal, Afrizal (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Children are the next generation who have child protection is currently one of the most discussed issues. is currently one of the most discussed issues. The condition of children there are still many who need attention. Various problems and cases that making children as victims have occurred in recent years. These problems can include discrimination, violence, exploitation, unreachable education processes that result in the child's education process that is unreachable resulting in the child dropping out of school, and neglect of the child. dropping out of school, and child neglect. Therefore, the protection of children becomes very important. This research was conducted with the aim of to determine the implementation of the Pekanbaru mayor's regulation number 33 of 2016 concerning the decent city policy. This research uses qualitative research methods qualitative research method by using data collection techniques of observation, interview and documentation. documentation. From the results of the research, it shows that the policy on child-friendly cities in Pekanbaru city has been implemented, but it is considered not yet feasible. worthy of children in the city of Pekanbaru has been implemented, but it is considered not optimal because there are still children's rights that have not been maximized. because there are still children's rights that have not been not fully fulfilled, such as there are still many violations of children's rights, in addition to the limited budget that is owned in supporting the implementation of this program.Â